1996
DOI: 10.1111/j.1468-3083.1996.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic urticarial papules and plaques of pregnancy (PUPPP): a clinicopathological review of 35 patients

Abstract: The clinical features of 35 cases of Pruritic Urticarial Papules and Plaques of Pregnancy (PUPPP) seen over an 8 year period were reviewed with regard to age and gestational stage of onset, evolution and severity of disease and response to therapy. The histologic features in biopsies from 15 patients were analysed for pattern and extent of inflammatory change and the composition of the inflammatory cells were studied with a panel of monoclonal antibodies. This study confirmed PUPPP to be a well defined clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The frequent occurrence of twin pregnancies in series of PUPPP cases has previously been noted, with incidences of twins of 9%, 11 10%, 4 11% 2 and 16% 5 reported. The occurrence of PUPPP in triplet pregnancies was first described by Beckett and Goldberg in 1991 6 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The frequent occurrence of twin pregnancies in series of PUPPP cases has previously been noted, with incidences of twins of 9%, 11 10%, 4 11% 2 and 16% 5 reported. The occurrence of PUPPP in triplet pregnancies was first described by Beckett and Goldberg in 1991 6 .…”
Section: Discussionmentioning
confidence: 69%
“…Histologically, PUPPP is described as a perivascular upper and mid‐dermal inflammatory infiltrate with epidermal spongiosis and vesiculation. The infiltrate is composed of a mixture of T lymphocytes and macrophages 2 . Direct immunofluorescence of perilesional skin is usually negative and haematological and biochemical tests show no consistent abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…The number of twin or multiple pregnancies in PEP seems to be significantly increased 11 . The frequent occurrence of twin pregnancies in series of PEP cases has been noted, with reported incidences of twins of 9%, 35 10%, 16 11% 8 and 16% 14 . In a recent study 11 of 44 women presenting with PEP, there were six sets of twins and one set of triplets.…”
Section: Clinical Presentationmentioning
confidence: 95%
“…The new term has the advantage of being both clinically accurate and also free from any misleading connotations; but in some quarters, disagreement persists about the presumed identity of PUPPP and PEP. Some suggest that the former is more narrowly defined by clinical findings than the latter 7,8 . Although, the term PUPPP is mostly used in the United States and PEP in Europe, it is generally agreed that PEP and PUPPP are identical dermatoses 5 …”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the activation of the skin immune system characterized by increased numbers of dentritic cells and activated T cells in lesional skin contribute to the pathology of PUPPP (29). Skin infiltrates of macrophages (30) and eosinophils (25, 27) have been described in affected tissue. Although, a direct implication of MCs has, as of yet, not been reported in PUPPP there are several lines of evidence that clearly suggest a role for MCs.…”
Section: Pruritic Urticarial Papules and Plaques Of Pregnancymentioning
confidence: 99%